MEDIA KARDUS BEKAS SEBAGAI ALTERNATIF PENINGKATAN KEMAMPUAN LOMPAT JAUH PESERTA DIDIK - Susilawati Bustaman (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT: This research is motivated by students who feel burdened with physical education lessons because physical abilities are needed in learning it. To present a concrete experience in a real form, especially in PJOK lessons, concepts or practices (physical management), a teacher should use media / teaching aids so that the learning experience that students have is truly real and well stored in the students' understanding.This research is classified as classroom action research, with four main steps, namely: action planning, action, observation, and reflection, involving students as samples at SMP Negeri 01 Muara Bungo.The results of the study concluded that by using used cardboard props (KB), the ability of students quantitatively in the form of long jump abilities and qualitatively in the form of interest, attention, participation and presentation of students increased. The average score of the long jump ability of students from cycle I to cycle 2 increased. In addition to the average score of students' learning completeness from cycle I to cycle II, there was also an increase. This is due to the use of used cardboard props (KB) with improved classroom management which is better carried out in groups. Keywords: media, used cardboard, long jump